Acroosteolysis of distal phalanges in patient with systemic sclerosis - case report - Zofia Gerlicz-Kowalczuk; Zbigniew Pietrzak; Jolanta D. Torzecka; Anna Woźnicka; Bożena Dziankowska-Bartkowiak (Termedia Publishing House, 2016)
Introduction. Acroosteolysis is a recognized, but under-researched and forgotten manifestation of systemic sclerosis (SSc). Objective . To present a case of exuberant acroosteolysis and subcutaneous tissue calcinosis in the course of SSc. Case report. The patient, aged fifty-three with limited systemic sclerosis (lSSc) for 8 years duration, was under dermatological treatment because of ulcerative inflammation of the 2nd and 4th finger of the right hand. Progressive acroosteolysis of the distal phalanx with calcinosis and severe digital ischaemia was diagnosed. Conclusion . There is growing evidence suggesting that acroosteolysis is an important manifestation of SSc due to the correlation with progressive microangiopathy and severity of digital ischaemia.